An awareness advertising humanity drive for Rohingya / Alisa Marni Ali - Marni Ali, Alisa (Faculty of Art and Design, 2013)
The awareness campaign about humanity’s drive for the Rohingya community using advertising is the main issue of this topic. This research describes the people awareness in Malaysia against the violence faced by Rohingya. Some donation has been received to help the Rohingya community in Arakan, Myanmar. In this research, the advertising was considered to be used in order to get people’s attention. The important of this advertising is to gain sympathy and concern from the public so that the next generation will be following the same footsteps.